Protective Effect of CXCR3+CD4+CD25+Foxp3+ Regulatory T Cells in Renal Ischemia-Reperfusion Injury - Cao Jun; Li Qingshu; Wei Ke; Li Ping; Dong Jun; Luo Jie; Min Su (Hindawi Limited, 2015)
Regulatory T cells (Tregs) suppress excessive immune responses and are potential therapeutic targets in autoimmune disease and organ transplantation rejection. However, their role in renal ischemia-reperfusion injury (IRI) is unclear. Levels of Tregs and expression of CXCR3 in Tregs were analyzed to investigate their function in the early phase of renal IRI. Mice were randomly divided into Sham, IRI, and anti-CD25 (PC61) + IRI groups. The PC61 + IRI group was established by i.p. injection of PC61 monoclonal antibody (mAb) to deplete Tregs before renal ischemia. CD4+CD25+Foxp3+ Tregs and CXCR3 on Tregs were analyzed by flow cytometry. Blood urea nitrogen (BUN), serum creatinine (Scr) levels, and tubular necrosis scores, all measures of kidney injury, were greater in the IRI group than in the Sham group. Numbers of Tregs were increased at 72 h after reperfusion in kidney. PC61 mAb preconditioning decreased the numbers of Tregs and aggravated kidney injury. There was no expression of CXCR3 on Tregs in normal kidney, while it expanded at 72 h after reperfusion and inversely correlated with BUN, Scr, and kidney histology score. This indicated that recruitment of Tregs into the kidney was related to the recovery of renal function after IRI and CXCR3 might be involved in the migration of Tregs.